(untitled) - Clouse, Barbara Fine (Boston, 2003)
Patterns for a Purpose is a rhetorical reader that shows students how to use the rhetorical patterns—either alone or in combination—to achieve various writing purposes. It continues to emphasize critical reading and thinking, to offer detailed coverage of the writing process, to provide a rich variety of writing opportunities, to emphasize argumentation and persuasion, and to provide reading selections, both classic and contemporary, that function as models as well as springboards for discussion and writing.
Keywords: College readers,English language,Report writing; Rhetoric